Tekstualiteit van kinematografie: Filmhermeneutiek as publieke teologie - Dreyer-Kruger, AnetElizabeth (HTS teologiese studies, 2014)
Tendencies in film hermeneutics. Hollywood is synonymous with the tradition of images that are used to create emotion, to strengthen attachment, and to encourage imitation. In a certain sense these values are also encouraged by the church as institution. Scholars who study the connection between cinematography and theology acknowledge that the cinema has become the ‘principal new church’ for post-secularised believers. Films are regarded among the ‘big books’ of ‘postmodern culture’. In this article it is argued that film hermeneutics should be regarded as an epistemological movement which has departed from a typographical culture, including logocentrism, phonocentrism, and text-focused cognition. The movement is towards a visual culture, including audiovisual and virtual realities, and is contextualised in a cyber-community. Tendencies in films with biblical and religious dimensions and themes, including the way in which the Christ figure is portrayed, are discussed. In this article the value of film hermeneutics – that is, the ‘textuality of the screen’ – as public theology, is also identified.